Suppression of common blight disease (Xanthomonas axonopodis pv. phaseoli) by a bacterial endophyte in soybean (Glycine max) - MAGESHWARAN, V; VITAL, L; ANNAPURNA, K (The Indian Journal of Agricultural Sciences, 2012)
Soybean seeds inoculated with Paenibacillus polymyxa HKA 15, a bacterial endophyte of soybean showed higher germination percentage, root length, shoot length, vigour index and biomass compared to uninoculated seeds. The crude metabolite from P. polymyxa HKA 15 showed a clear zone of inhibition against strains (M 5 and CP 1-1) of bacterial common blight pathogen X. axonopodis pv. phaseoli in agar diffusion assay. Under poly house conditions, the effect of P. polymyxa HKA 15 on seed germination percentage and biocontrol activity against bacterial common blight disease was assessed. Soybean seeds treated with P. polymyxa HKA 15 showed significant increase in seed germination percentage compared to untreated seeds. Pin-prick inoculation of strains of X. axonopodis pv. phaseoli, strains, viz CP 1-1 and M 5 on soybean leaves treated with endophyte resulted in lowest mean disease ratio (MDR) of 0.80 and 0.88 at two DAI and 1.24 and 1.1 at four DAI and per cent disease incidence (PDI) of 16 and 17.6 at two DAI and 24.8 and 22 at four DAI respectively.